Réponses

Meilleure réponse !
2013-04-30T15:26:47+02:00

a) 2x+2=5+x            

     2x-x=5-2

     x=3

 

b) -3+2x=4-5x

      2x+5x=4+3

      7x=7

       x=1

 

c)  6x+2=x+12

      6x-x=12-2

      5x=10

       x=2

 

d)  3x+3=-x-1

      3x+x=-1-3

       4x=-4

       x=-1

 

e) 3x+7=x+2

     3x-x=2-7

     2x=-5

      x=-5/2

 

f) 2+2y=-1+3y

    2y-3y=-1-2

    -y=-3

    y=3

  

2013-04-30T15:33:00+02:00

a) x = 3

c) 6x-x = 12-2

    5x = 10

    x = 10/5

    x= 2

e) 3x-x = 2-7

     2x = -5

      x= -5/2

      x = -2.5

 

b)  2x+5x = 3+4

      7x = 7

      x= 7/7

      x= 1

 

d) 3x +x = -3-1

    4x = - 4

    x= -4/4

    x = -1

 

f) 2y - 3y = -2 -1

   -1y = - 3

     y = -3/-1

     y = 3